Fluorescence-guided minimally invasive parathyroidectomy: clinical experience with a novel intraoperative detection technique for parathyroid glands - Proßt, Rüdiger Lothar; Weiss, Johannes; Hupp, Linus Christian; Willeke, Frank; Post, Stefan (World journal of surgery, 2010)
Background: Detection of normal and pathologic parathyroid glands often is difficult due to their variability in number and location. We have implemented photosensitizer-induced fluorescence for the routine intraoperative identification of parathyroids for the surgical treatment of hyperparathyroidism. Methods: From 2004 to 2007, 25 patients suffering from primary and secondary hyperparathyroidism underwent minimally invasive videoscopic-assisted parathyroidectomy after oral photosensitization with aminolevulinic acid (ALA). Results: Fluorescence was sufficiently strong in 48% of patients to aid faster detection of the glands in situ. In an additional 44%, the fluorescence behavior supported the identification of the glands in situ and after excision, yielding a total of 92% of glands whose identity could be confirmed by the fluorescence technique.Conclusions: Fluorescence-guided minimally invasive parathyroidectomy is technically feasible and may support the surgeon in detecting and confirming the parathyroid glands. As the fluorescence method requires only moderate additional technical efforts and clinical expenditure, it is a valuable add-on component in parathyroid surgery to facilitate the operation.